2007
DOI: 10.1139/t06-089
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of a municipal landfill slope failure near Cincinnati, Ohio, USA

Abstract: The March 1996 slope failure in a municipal solid waste landfill near Cincinnati, Ohio, USA, is reanalyzed using continuum-mechanics-based procedures implemented in the computer programs FLAC and FLAC3D. A failure mechanism, based on the field observations of the failure, is used for the analyses. The failure mechanism is also implemented in a limit-equilibrium-based slope stability analysis computer program, SSTAB2, to simulate the observed translational character of the failure. The reanalysis results (failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The Kettleman landfill slope failure of 1988 was back-analyzed using a threedimensional approach derived from the observed sliding-block mechanism by Chang (2005). Chugh et al (2007) back-analyzed the slope failure of a MSW landfill near Cincinnati, Ohio, USA, using a continuum mechanics-based procedure that was implemented in the computer programs FLAC and FLAC3D. These analysis results were generally consistent with the field data.…”
Section: Introductionmentioning
confidence: 65%
“…The Kettleman landfill slope failure of 1988 was back-analyzed using a threedimensional approach derived from the observed sliding-block mechanism by Chang (2005). Chugh et al (2007) back-analyzed the slope failure of a MSW landfill near Cincinnati, Ohio, USA, using a continuum mechanics-based procedure that was implemented in the computer programs FLAC and FLAC3D. These analysis results were generally consistent with the field data.…”
Section: Introductionmentioning
confidence: 65%
“…However, the interpretations of the former studies were only based on visual observations by eyewitnesses, whereas the methods we used combined both eyewitness accounts and a field analysis of the internal structure of the waste deposits. This original approach for this kind of study allows us to state that both sliding and flow processes were involved during the 2005 waste Bernardo (2004); Merry et al (2005); Palaypayon and Ohta (2006); Gaillard and Cadag (2009) Leuwigajah, Bandung, Indonesia 2005 147 This work;Koelsch et al (2005) Belo Horizonte, Brazil 1992 > 100 http://www.humanite.presse.fr /journal/1992-03-20/1992-03-20-650098 Istanbul, Turkey 1993 39 Kocasoy and Curi (1995); Koerner and Soong (2000); Huvaj-Sarihan and Stark (2008) Bantargebang Koelsch et al (2005) Bulbul, Durban, South Africa 1997 Blight (2004Blight ( , 2008 Iriya, Tel-Aviv, Israel 1997 - Isenberg (2003); Isenberg et al (2004); Huvaj-Sarihan and Stark (2008) Doña Juana, Bogota, Colombia 1997 -GeoSyntec Consultants (1998); Hendron et al (1999); Caicedo et al (2002) ; Gonzales Garcia and Espinosa Silva 2001Bens, Coruña, Spain 1996 - Landva and Dickinson (2000) Rumpke, Cincinnati, Ohio, USA 1996 -Eid et al 2000; Chugh et al (2007); Evans & Stark (1997); Schmucker and Hendron (1998) Leuwigajah, Bandung, Indonesia 1992 -Personal field data Kettleman, California, USA 1988; Seed et al (1990); Byrne et al (1992); Chang (2005) Sarajevo, Bosnia 1977 - Gandolla et al (1979) Bandeirantes, Saõ Paulo, Brazil 1991 - Bauer et al (2008) avalanche at Leuwigajah. The type of movement, however, may be of different type depending on the internal structure of the material deposited in the dump and the origin of motion.…”
Section: A Difficulty To Assess Motion Processes Of Waste Avalanchesmentioning
confidence: 99%
“…A mixture of peat, kaolinite, and quartz sand was used in laboratory tests to study the interplay between water content of filling and MSW failure, of which the results shown that, with increased water content of the MSW, the mobility increases while the maximum and final flow depth decrease (Dai et al, 2016). Numerical simulation has been widely used in landfill slope stability analysis (e.g., Chang, 2002Chang, , 2005Chugh et al, 2007;Huang and Cheng, 2017); some of the more advanced methods include the application of the smoothed-particle hydrodynamics (SPH) method (e.g., Huang et al, 2013) and the moving-particle semi-implicit (MPS) method (e.g., Huang and Zhu, 2014) for runout distance analysis of landfill flowslide.…”
Section: Introductionmentioning
confidence: 99%